A study on the factors that contribute to truancy among secondary school students in Sekolah Menengah Kebangsaan Taman Ria, Sungai Petani, Kedah / Nuratikah Jeffry and Nur Amalina Syazana Ayob - Jeffry, Nuratikah; Ayob, Nur Amalina Syazana (2017)
Truancy can be defined as the student that absent from school or skip the class without any notice or proper reason. Truancy can lead to serious issues such as vandalism, gangsterism and any crime action. Truancy should be taken seriously by all parties because the youngster is the one that will lead in the future generation. Ministry of Education had mention that about more than 20000 students played truancy in 2007 and it becomes more serious year by year. There are several factors that contribute to truancy among secondary school students’. By conducting this study, the researcher found that the factor that contributes to truancy are family factor, school factor and peers factor. This study will use quantitative method and will be conducted through stratified sampling technique. A sample of 144 students in Sekolah Menengah Kebangsaan Taman Ria, Sungai Petani, Kedah will be selected to answer the questionnaire.